Effect of biomass smoke on chronic obstructive pulmonary disease in rural localities of colombia: a cross-sectional study (2013)
Objectives The aim of this study was to assess the differences associated to the change of biofuel used to cook as a way to estimate the proportion of respiratory abnormalities of respiratory function associated to biomass exposure.Methods A cross-sectional study was designed to evaluate the respiratory function through spirometry in subjects cooking with biomass or natural gas. All patientswere evaluated by a general physician and a pulmonologist. We compared the prevalence of spirometry abnormalities across those cooking with natural gas versus those cooking with biofuel. A multivariable logistic regression and multiple linear regression were used to adjust differences by potential confounding factors.Results 203 subjects were studied. There was a significant increase in the prevalence of severe obstructive pattern (OR 5.50; 95 % CI 1.17-25.79) in subjects who cook with biomass compared with natural gas users. Values of forced expired volume in one second (FEV1) and forced vital capacity (FVC) were statistically lower among those cooking with biomass. The prevalence of respiratory morbidity and symptoms were not statistically significant between both groups.Conclusions These findings suggest that replacing biomass fuel by natural gas may be an important public health intervention in Colombia, because it can reduce the prevalence of abnormal patterns of pulmonary function.